Modern methods in crop protection research - Jeschke, Peter (Wiley-VCH, 2012)
This handbook and ready reference highlights a couple of basic aspects of recently developed new methods in modern crop protection research, authored by renowned experts from major agrochemical companies. Organized into four major parts that trace the key phases of the compound development process, the first section addresses compound design, while the second covers newly developed methods for the identification of the mode of action of agrochemical compounds. The third part describes methods used in improving the bioavailability of compounds, and the final section looks at modern methods for risk assessment. As a result, the agrochemical developer will find here a valuable toolbox of advanced methods, complete with first-hand practical advice and copious examples from current industrial practice.